Artemisia argyi polysaccharide ameliorates hyperglycemia through modulating gut microbiota and serum metabolism in type 2 diabetic mice - Qiaoying Song; Hankui Wu; Shaoting Weng; Yao Wang; Lingqi Kong; Ziqing Liu; Kunpeng Zhang (Journal of Functional Foods)
In this manuscript, we investigated the hypoglycemic effect and mechanism of Artemisia argyi polysaccharide (ALP-1) on high-fat diet/streptozotocin-induced diabetes mice. After 4 weeks of oral administration of ALP-1, the HALP-1 diabetic mice group showed a 27.2 % reduction in liver index, a 10.3 % decrease in fasting blood glucose, and a 14.19 % decrease in glycated serum protein compared to the DM group. Additionally, improvements were observed in oxidative stress, inflammatory response, and serum insulin levels. Furthermore, the HALP-1 group exhibited enhanced glucose tolerance, liver glycogen level, and insulin sensitivity. Moreover, ALP-1 could increase the abundance of SCFAs, especially n-butyric acid in intestinal contents and faeces of diabetes mice. Intestinal flora results showed that ALP-1 treatment increased the abundance of genus Allobaculum in the cecum of diabetic mice. The results of fecal microbiota transplantation and antibiotics treatment confirmed that ALP-1 exerts hypoglycemic effect through regulating intestinal flora to a certain extent. The findings of our investigation indicate that ALP-1 has the potential of ameliorate hyperglycemia through modulating gut microbiota and serum metabolism.